Determination of two-photon photoactivation rates of fluorescent proteins - Hartwich, Tobias Max Philipp (Physical chemistry, chemical physics, 2013)
The application of two-photon activation of photoactivatable fluorescent proteins is limited by a lack of information about two-photon activation rates. Here we present rates for the commonly used photoactivatable proteins PAmCherry, PAmKate and PA-GFP at different wavelengths using a novel method that allows us to determine the two-photon activation rates directly, independent of any reference data, with microscopic sample volumes. We show that PAmCherry features the highest rates of the tested proteins at 700 nm activation wavelength followed by PAmKate. Towards longer wavelengths, two-photon activation rates decrease for all three proteins. For PAmCherry, our data contradicts an activation model relying solely on two-photon activation and suggests additional activation pathways requiring at least two absorption steps. Our method is readily expandable to other photoactivatable fluorescent molecules. The presented results allow optimization of experimental conditions in spectroscopic and imaging techniques such as super-resolution fluorescence microscopy.
Gesehen am 08.10.2021